2006
DOI: 10.1007/s10973-005-6939-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of iminodiacetic, oxydiacetic and thiodiacetic acids

Abstract: The thermal decomposition of iminodiacetic, oxydiacetic, and thiodiacetic acids in helium atmosphere has been studied by means of thermogravimetry (TG), differential thermal analysis (DTA) and temperature-programmed pyrolysis directly coupled with mass spectrometry (TPPy-MS). Evolved gas analysis (EGA) profiles of iminodiacetic and oxydiacetic acids were obtained and compared with TG and DTA profiles. The decomposition of iminodiacetic acid forms water, CO, CO2, CH3CN, HCN and some hydrocarbons. After water ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The weight loss continues slowly even at higher temperature with the loss of 1.2% more, which reflects most probably the cracking of the residual surface alkyl siloxane species. 27 The thermal decomposition of the pure iminodiacetic acid investigated by the TGA-MS method 28 (see also Fig. FS3 † for the TGA-FTIR data obtained in this work) occurs in a highly reproducible manner in 3 steps, where the first step at 217-252 °C is associated with the release of water through the formation of an anhydride, the second step at 280-338 °C is associated with the decarboxylation of the anhydride with the release of CO 2 and the third less defined step at 400-600 °C corresponds to the cracking of the residual material.…”
Section: Surface Bonding and Compositionmentioning
confidence: 99%
“…The weight loss continues slowly even at higher temperature with the loss of 1.2% more, which reflects most probably the cracking of the residual surface alkyl siloxane species. 27 The thermal decomposition of the pure iminodiacetic acid investigated by the TGA-MS method 28 (see also Fig. FS3 † for the TGA-FTIR data obtained in this work) occurs in a highly reproducible manner in 3 steps, where the first step at 217-252 °C is associated with the release of water through the formation of an anhydride, the second step at 280-338 °C is associated with the decarboxylation of the anhydride with the release of CO 2 and the third less defined step at 400-600 °C corresponds to the cracking of the residual material.…”
Section: Surface Bonding and Compositionmentioning
confidence: 99%
“…The first weight loss (obsd, 34.71%; calcd, 34.74%) occurs in the range of 200-310 ºC, corresponding to the decomposition of the Hydet-en ligand. While the free oxydiacetic acid loses in the temperature range 160-250 ºC 27 , the complex loses the carboxylate in the temperature range 375-570 ºC. The experimental mass loss in this stage is 37.39% (calcd, 38.69%).…”
Section: Ft-ir Spectramentioning
confidence: 89%
“…The lactonic and phenolic group contents compensate each other at reaction temperatures of 180, 200 and 220 C: the increase in the reaction temperature leads to an increase in the lactonic functionality and a decrease in phenolic groups; however this pattern was reversed when the reaction temperature increased from 220 to 250 C. Vinciguerra et al have demonstrated the thermal behaviour of IDA in their previous work. 49 The work suggested that IDA undergoes a mass loss, which is attributed to the loss of water and the formation of iminodiacetic anhydride, at 217-252 C. During this process, little evolution of CO 2 can also be observed, which is considered as an indication of a partial decarboxylation process. An even more complex thermal degradation mechanism was reported by González Vílchez et al, where the increasing temperature promotes the breaking of hydrogen bonds and the loss of 2H 2 O molecules per 2 bonded IDA molecules.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%